Neural and Endocrinal Pathobiochemistry of Vitiligo: Comparative Study for a Hypothesized Mechanism - Kotb El-Sayed, Mohamed-I.; Abd El-Ghany, Ahmed A.; Mohamed, Refaat R. (Frontiers in Endocrinology, 2018)
The etiology of vitiligo is still unclear. The aim is to investigate a neural and hormonal etio-pathology of vitiligo. Sixty acrofacial vitiligo patients were divided into two subgroups as active vitiligo patients group (AVPs; n = 35) and stable vitiligo patients group (SVP; n = 25). Forty healthy subjects without any systemic or dermatological disease were used as controls. Blood samples were collected, and the samples were used for measurement of free triiodothyronine (fT3), free thyroxine (fT4), thyroid-stimulating hormone (TSH), adrenocorticotrophic hormone (ACTH), cortisol, estrogen, testosterone, melatonin, and prolactin levels by ELISA, while norepinephrine (NE), epinephrine (Epi), dopamine (DA), homo-vanillic acid (HVA), serotonin, and 5-hydroxyindoleacetic acid (5-HIAA) by high-pressure liquid chromatography. The current results showed a significant increase in plasma levels of Epi, NE, DA, HVA, serotonin, 5-HIAA, melatonin, and in serum level of TSH and prolactin either in SVP or AVP groups than the control group and in AVP than SVP group. The serum levels of fT3 and fT4 were significantly decreased either in SVP or AVP groups than the control group. A significant increase in estradiol levels was observed in females within AVP than females in either SVP or control groups. There was a significant increase in serum level of cortisol in AVP than either SVP or control group. There was a significant decrease in serum level of ACTH in either AVP or SVP than control and in AVP than SVP group. In conclusion, there are some neural and endocrine markers that play a pivotal role in pathogenesis and/or consequences of vitiligo. The abnormally disturbed levels of theses markers lead to melanocyte destruction and/or depigmentation.